Natural Convection Of A Casson-Type Nanorefrigerant Along A Vertical Plate Embedded In Dispersive Porous Medium - Nada, Hamza; Bouaziz, Amina Manal; Bouaziz, Mohamed Najib (Zielona Góra: Uniwersytet Zielonogórski)
To address the use of nanorefrigerants of recognized environmental interest, this research focuses primarily on the impacts of thermal dispersion and inertia effect of porous medium. Combined with nanoparticles in natural convection of Casson base nanofluid flow on an embedded vertical plate, heat transfer is then examined. Using technical similarity, the ordinary differential equations resulting from the transformation of the partial differential equations are solved by the III Lobatto discretization of finite differences method through bvp4c @Matlab.
Keywords: nanorefrigerant; Casson; porous media; dispersion; natural convection